Development of Magic Paper Models to Improve Dental Health Behavior among Children with Elementary School Level - Rifa Fauziah Syaifia Putri; Rasipin Rasipin; Tri Wiyatini; Ari Suwondo; Suharyo Hadisaputro (International Journal of Nursing and Health Services (IJNHS), 2020)
The prevention of dental diseases and mouth has been done with many preventive and curative promotive efforts. Still, the effort has not succeeded in increasing the value of dental health behavior. It is seen from the percentage of caries of children aged 9-11 years by 44%. Elementary school children's media can help understand, maintain, and prevent dental and oral diseases. The media was created in an exciting form so that the child was able to learn while playing. Generating magic paper models produced by the design of relevant/worthy builds as health promotion media for children, and its application can improve elementary school children's dental health behavior better. A research and Development (R&D) research design was applied in this study and model testing using quasi-experiment design pre-test and post-test with non-equivalent control group design. Magic paper models are relevant/feasible as a media for health promotion for elementary school children. The 21 days program was useful for an increase in knowledge (P=0.001), attitude (P=0.001), and action (P=0.001) on health promotion for elementary school children. Media Magic paper models created by the design of the relevant/feasible as health promotion media for children and its application can better improve dental health elementary children's behavior